Thermal requirements of seed germination of ten tree species occurring in the western Brazilian Amazon - Felipe Daibes, L. F. [UNESP]; Amoêdo, Semirian C.; Nascimento Moraes, Jeane Do; Fenelon, Natália; Da Silva, Débora Rosa; De Melo Lopes, Max Jr; Vargas, Lidiane A.; Monteiro, Ediléia F.; Frigeri, Renita B.C. (Cambridge University Press (CUP), 2019)
Regeneration from seed affects species assembly in plant communities, and temperature is the most important environmental factor controlling the germination process. Thermal dependence of seed germination is thus associated with species occurrence in an ecosystem. Hence, we aimed to investigate the role of temperature on seed germination of ten tree species from the western Brazilian Amazon. Seeds were collected in the state of Rondônia, Brazil, and set to germinate under constant temperatures ranging from 10 to 40°C in germination chambers. We calculated germination capacity (G%), germination rate (GR50, reciprocal of germination time), and thermal parameters, such as cardinal temperatures and thermal time requirements. Most species had a large range of temperatures showing G% ≥80%, with optimal temperature varying from 20 to 40°C. Base temperature ranged from 6 to 12°C and ceiling temperatures were mainly >40°C. Astronium lecointei and Parkia nitida showed high germination capacity under temperatures of 35-40°C, while germination of Theobroma cacao dropped from 100% to zero under temperatures between 37 and 40°C. The climax species Cedrela fissilis had the slowest germination time (10 days) and highest thermal time requirement, while seeds of Enterolobium schomburgkii (a late-successional species) germinated within the first day of the experiment. Rapid recruitment of Amazon species could be favoured with treefall disturbance, which increases temperatures in the understory, but sharp limits might be found in the supra-optimal range of temperatures. Such patterns might indicate different regeneration strategies in the tropical rainforest, providing important information regarding seed germination among Amazon species.
Keywords: Amazonia; cardinal temperature; rainforest; regeneration niche; temperature; thermal time; tropical forest